Information Management Systems in the Supply Chain - Sousa, M.; Cruz, R. V.; Caracol, C; Dias, I. (Supply chain and logistics management: Concepts, methodologies, tools, and applications, 2020)
This chapter analyzes the importance of technologies as drivers for managing supply chains. The focus will be on the advantages of the use of information technologies to improve company's efficiency to be competitive and for the reduction of costs, improvement of operations, improvement of relationships with customers, suppliers and partners, shortening of delivering times, streamlining and optimization of business processes and operations. The use of new technologies contributes to improve efficiency of supply chain management: raw material suppliers, component manufacturers, finished product manufacturers, wholesalers and retailers. Technologies allow an integrated approach to planning, control and monitoring of product flows, from suppliers to end users. They aim at improve customer service at reduced overall costs, and leads to the development of important relationships with logistics providers, suppliers, and customers in order to enhance information exchange and the coordination of business activities, which are the key advantages of an integrated supply chain with the collaboration among all the participants in the value chain.